INSIGHT INTO ANTIMICROBIC EVALUATION TECHNIQUES AND THEIR ROLE IN BETTER ASSESSMENT OF ANTIMICROBIC AGENTS: A REVIEW - DOGRA, DEEKSHA; JULKA, JM.; KUMAR, ARUN (Asian Journal of Pharmaceutical and Clinical Research, 2022)
At present, researchers have a keen interest in creating advanced antimicrobic agents to overcome microbial resistance from various new sources either from plants or microbes. For this, robust attention has been given to the advancement in the rapid antimicrobic assessment strategies and methods to develop antimicrobic agents. Some of the antimicrobic techniques such as well diffusion using broth and agar and disc diffusion are more prominent in assaying antimicrobial testing while techniques such as bioluminescence, flow cytofluorometry methods are less used due to specific equipment’s, high calibration and evaluation processes. Thus, the information of precise antimicrobial techniques is must to the new researchers for antimicrobic testing. In this review article, various antimicrobic techniques with their advantages and limitations are being reported which are currently being carried out for antimicrobial testing.